2011
DOI: 10.1080/03079457.2011.605782
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of infectious bronchitis virus isolates from Russia and neighbouring countries: identification of intertypic recombination in the S1 gene

Abstract: Infectious bronchitis virus (IBV) isolates recovered in Russia, Ukraine, and Kazakhstan between 2007 and 2010 were subjected to molecular characterization and compared with those isolated a decade ago. The IBV genome was detected in 202 out of 605 field samples from chickens with various clinical signs. Partial sequencing of the S1 gene revealed 153 vaccine strains and 49 field isolates of several genetic groups. Massachusetts, 793/B and D274 remained the predominant IBV genotypes along with QX, whereas B1648,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that the side effects of the 4/91 vaccine might provide the basis for recombination with other strains. This phenomenon has been shown by several studies which have traced the emergence of many novel IBV strains to recombination events between the 4/91 vaccine and field strains (Feng et al, 2018;Han et al, 2017;Jiang et al, 2017Jiang et al, , 2018Liu et al, 2013;Mo et al, 2013;Ovchinnikova et al, 2011;Zhang et al, 2015Zhang et al, , 2016Zhou et al, 2017) in cases where the 4/91 vaccine strain could not provide effective protection against the field strains , leading to coinfection of the vaccine and field strains in the same chickens and ultimately resulting in recombination. In this study, we performed complete genome sequence analysis of strains I0718/17, I0722/17, I0724/17, and I0737/17 and confirmed the occurrence of recombination events at the 5′ ends of the S1 gene between a 4/91-like virus (GI-13 lineage) and a YX10-like virus (GI-19) (Xu et al, 2018), which contributed to the emergence of the IBV strains.…”
Section: Discussionmentioning
confidence: 87%
“…Recombination is involved in the emergence and evolution of IBV or can even directly lead to the emergence of new coronaviruses and related diseases [36] Recombination can occur between field isolates or between field and vaccine viruses [36,37,38]. In our study, convincing evidence showed five S1-gene recombinants GX-NN8, GX-NN9, GX-NN10, GX-NN11 and GX-YL7, with their putative parental strains of vaccine strain 4/91 and CK/CH/LSC/99I-Type field strain GX-YL2, and their crossover regions were at nucleotide position 7–677 or 7–678.…”
Section: Discussionmentioning
confidence: 99%
“…D274 was detected in Sweden, England and Russia in 1995, 1996 and 1998, respectively [28]. Several reports have been confirmed D274 presence in Western Europe from 2002 to 2006 [19,29,30]. D274 was not detected in the Middle East countries before 2005, its first report from Jordan [31].…”
Section: Discussionmentioning
confidence: 95%